DESIGNING A MOTION COMIC â€œPERJALANAN PECILâ€ FEATURING KEDIRIâ€™S SIGNATURE SAMBAL TUMPANG TO SHOWCASE THE CULINARY DELIGHTS OF KEDIRI - Handaru, Wuri Cahya; Hamida, Mayliana Wahyu (Fakultas Vokasi Universitas Brawijaya, 2024)
Abstract: Sambal tumpang is a Javanese specialty. In Central Java, sambal tumpang is quite famous in several areas such as Solo, Klaten, Salatiga, Sragen, Boyolali, and Wonogiri. In East Java, the most famous area with sambal tumpang is Kediri. This research aims to introduce Kediri sambal tumpang as a typical food of Kediri City. This is because there are similarities in the use of sambal tumpang as a specialty food from other regions in Central Java. Based on observations made in the pecel tumpang Pudakit area Jl. Dhoho Kediri, it is known that teenagers with an age range of 15 - 20 years still have little interest in this typical Kediri sambal tumpang. Therefore, the target audience of the motion comic design